Understanding Bangladeshi Female Garment Workers’ Experience: Empowerment, Patriarchy and Emotional Wellbeing - Sultana, Habiba; Rahman, Habiba; Mazumder, Sumon Kumer (Social Science Review, 2025)
This paper explores the experiences of Bangladeshi female garment workers in relation to patriarchy, empowerment, and emotional wellbeing. While some research highlights the positive impact of paid work on women’s status, others note the ongoing challenges of balancing employment, domestic responsibilities, and exposure to violence at home and work. This article argues that although garment work has improved workers' economic conditions, it contributes to anxiety and diminished emotional well-being due to separation from children. Additionally, while paid employment in the Ready Made Garment (RMG) sector has enhanced women's consumption capacity, many still adhere to patriarchal norms by relinquishing income to husbands and not owning assets in their names. Understanding economic empowerment within the contexts of patriarchy and emotional well-being is crucial for holistically assessing garment workers' experiences. Social Science Review, Vol. 42(1), June 2025, pp. 63-78